The effectiveness of marketing activities done by FAMA towards agricultural products: Case study in Pasar Tani Alor Setar / Shahida Abu Bakar - Abu Bakar, Shahida (Faculty of Business and Management, 2005)
The Malaysian agricultural industry is a smallholder-based industry or in Small and Medium Industries (SMI) involving 270, 000 farmers. FAMA involved directly in buying and selling the agricultural products. Through these activities, FAMA may create more markets for these entrepreneurs and build up competition in the market. These focused activities are to prevent the marketing problems and developing agriculture-based marketing in domestic market. The marketing activities done by FAMA are important in order to enhance the economic development by building and increasing customer awareness towards the agricultural products. In supporting the new focus on this sector, the government will also improve supporting infrastructure including distribution systems, marketing and promotion, incentives and accessibility to financing Thus, this study is interested to evaluate the effectiveness of marketing activities done by FAMA in enhancing customer awareness Inwards agricultural products, particularly in the district 0 Kota Setar. For the purpose 0 this study, the descriptive research will be deployed. Sample 0 the population was determined by using convenience technique. Primary data will be obtained from a survey by interviewing using questionnaires to 30 respondents, beside personal interview. Most of the secondary data was taken from FAMA Annual Report, previous research report and journals. All data collected from respondents were transferred onto datasheet by using computer software known as Statistical Program for Social Science (SPSS) a handy desktop statistical tool. Finally, the finding from this study is to conclude the level of effectiveness of marketing activities done by FAMA in enhancing customer awareness towards local agricultural products. Hence FAMA, whether must need to or does not to, redesign the design the combination of its marketing mix in order to maintain or improve its performance.